Composite material plate as well as preparation method and application thereof
By adopting a laminated structure and spray coating method in the composite material plate and fixing it through fiber nails, the problem that existing composite material bottom guard plates are difficult to pass in high-energy impact and high-temperature fire tests is solved, and excellent impact resistance and explosion-proof performance is achieved, which improves the safety of new energy vehicles.
Patent Information
- Application Number
- CN202411942753.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-28
AI Technical Summary
The existing composite bottom guard plate is difficult to pass in a 400J drop hammer impact test and a 1200°C×360s fire test, and lacks excellent explosion-proof performance.
The lower skin layer, polymer foam core material layer and upper skin layer are stacked in sequence from bottom to top, and the impact-resistant coating and refractory coating are sprayed in sequence on the outer surface, and fixed by fiber nails to form an integral frame structure to improve interlayer performance and impact resistance.
This composite plate can be kept intact during the hammer impact test of above 400J, and has certain anti-explosion ability. It can maintain structural integrity in the fire test of 1200℃×360s, significantly improving the safety of new energy vehicles.
Smart Images

Figure HDA0005213467230000011 
Figure HDA0005213467230000012 
Figure HDA0005213467230000021
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery protection, and in particular to a composite material plate and a preparation method and application thereof. Background Art
[0002] At present, most new energy vehicles use aluminum alloy lower boxes. During the driving process, if the bottom of the vehicle collides with foreign objects, when the battery lower box is pierced by foreign objects, once the battery liquid cooling plate or battery cell is damaged, it will easily cause the battery cell to catch fire, and then cause thermal runaway, which will bring great safety risks to the passengers. Therefore, the bottom guard plate equipped with the battery lower box can effectively provide physical protection and protect the battery cell system; at the same time, the bottom guard plate can prevent mud, rainwater and snow water containing snow melting agent from directly corroding the battery pack lower box.
[0003] Most existing underbody guards are made of metal materials such as steel and aluminum alloy, but in order to reduce the weight of the entire vehicle, lighter composite materials are also being used to manufacture underbody guards. The structure of the current composite underbody guard mainly includes an upper skin, a lower skin, and a thermoplastic composite material located between the upper skin and the lower skin. However, the composite underbody guard of the above structure is difficult to pass the more stringent 400J drop hammer impact test and 1200℃×360s fire test. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a composite material plate and a preparation method and application thereof. The composite material plate can ensure that the bottom guard plate passes a 400J drop hammer impact test and a 1200°C×360s fire test and has excellent explosion-proof performance.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a composite material panel, comprising a lower skin layer 2, a polymer foam core material layer 4 and an upper skin layer 1 which are stacked in sequence from bottom to top;
[0007] The outer surface of the lower skin layer 2 is provided with an impact-resistant coating 6 and a fire-resistant coating 7 in sequence;
[0008] The polymer foam core material layer 4 is provided with a resin column 5, and both end surfaces of the resin column 5 are in contact with the upper skin layer 1 and the lower skin layer 2 respectively;
[0009] It also includes fiber nails 3 passing through the lower skin layer 2 , the polymer foam core layer 4 and the upper skin layer 1 .
[0010] Preferably, the impact-resistant coating 6 is a polyurea coating;
[0011] The thickness of the impact-resistant coating 6 is 0.5-3.0 mm.
[0012] Preferably, the thickness of the refractory coating 7 is 0.3 to 1.5 mm;
[0013] The refractory coating 7 includes a high expansion type refractory coating or an organic-inorganic type refractory coating.
[0014] Preferably, the top end of the fiber nail 3 does not exceed the upper surface of the upper skin layer 1, and the bottom end of the fiber nail 3 exceeds the lower surface of the lower skin layer 2;
[0015] The diameter of the fiber nails 3 is 0.2-1.0 mm, and the distance between two adjacent fiber nails 3 is 10-60 mm.
[0016] Preferably, the thickness of the lower skin layer 2 and the upper skin layer 1 are independently 1.5 to 3.0 mm.
[0017] Preferably, the lower skin layer 2 and the upper skin layer 1 independently include fiber fabrics and resin filled in the fiber fabrics;
[0018] The material of the fiber fabric includes one or more of glass fiber, aramid fiber, ultra-high molecular weight polyethylene fiber and basalt fiber;
[0019] The resin includes one or more of vinyl resin, epoxy resin and polyurethane resin.
[0020] Preferably, the thickness of the polymer foam core layer 4 is 3 to 15 mm;
[0021] The density of the foam core material in the polymer foam core material layer 4 is 70-200 kg / m 3 .
[0022] Preferably, the material of the polymer foam core layer 4 includes phenolic foam, polyethylene terephthalate foam, polyurethane foam or polymethacrylimide foam;
[0023] The diameter of the resin column 5 in the polymer foam core layer 4 is 0.5-3.0 mm, and the distance between two adjacent resin columns 5 is 20-100 mm.
[0024] The present invention also provides a method for preparing the composite material plate described in the above technical solution, comprising the following steps:
[0025] The lower skin, the sandwich foam with a through-hole structure and the upper skin are sequentially stacked and pre-fixed to obtain a preform;
[0026] implanting fiber nails into the preform, and sequentially performing glue injection and curing molding to obtain an intermediate structure;
[0027] The composite material plate is obtained by spraying an impact-resistant coating and a fire-resistant coating in sequence on the outer surface of the lower skin layer of the intermediate structure.
[0028] The present invention also provides the use of the composite material plate described in the above technical solution or the composite material plate prepared by the preparation method described in the above technical solution in new energy vehicles.
[0029] The present invention provides a composite material board, comprising a lower skin layer 2, a polymer foam core material layer 4 and an upper skin layer 1 stacked in sequence from bottom to top; the outer surface of the lower skin layer 2 is sequentially provided with an impact-resistant coating 6 and a fire-resistant coating 7; a resin column 5 is provided in the polymer foam core material layer 4, and the two end surfaces of the resin column 5 are in contact with the upper skin layer 1 and the lower skin layer 2 respectively; and also includes a fiber nail 3 passing through the lower skin layer 2, the polymer foam core material layer 4 and the upper skin layer 1. The composite material board of the present invention is fixed with fiber nails, which can significantly enhance the interlayer performance of the upper skin layer, the foam core material layer and the upper skin layer of the composite material. At the same time, the lower end of the fiber nail exceeds the bottom surface of the lower skin and penetrates into the impact-resistant coating, connecting the impact-resistant coating, the upper skin layer, the foam core material layer and the lower skin layer as a whole, greatly improving the bonding force between the laminated structure and the impact-resistant coating, and then can resist the drop hammer impact test with an energy of more than 400J, and even have a certain explosion resistance. This has a broad application prospect for improving the safety of new energy vehicles. It can be seen that the composite material plate of the present invention can simultaneously meet the technical requirements of weight reduction and resistance to a 400J drop hammer impact test and a 1200°C×360s fire test. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Schematic diagram of the structure of the composite material plate of the present invention, wherein 1 is an upper skin layer, 2 is a lower skin layer, 3 is a fiber nail, 4 is a polymer foam core layer, 5 is a resin column, 6 is an impact-resistant coating, and 7 is a fire-resistant coating;
[0031] Figure 2 This is a graph showing the effect of the composite material plate described in Example 1 in resisting a 400J drop hammer impact test;
[0032] Figure 3 This is a graph showing the effect of the composite material plate of Comparative Example 1 on resisting a 180J drop hammer impact test;
[0033] Figure 4 This is a 1200°C×360s fire test effect diagram of the composite material plate described in Example 1;
[0034] Figure 5 This is a 1200°C×360s fire test effect diagram of the composite material plate described in Comparative Example 1;
[0035] Figure 6It is a schematic diagram of the structure of the composite material plate described in Comparative Example 1, wherein 8 is an upper skin layer, 9 is a foam core material layer, and 10 is a lower skin layer. DETAILED DESCRIPTION
[0036] like Figure 1 As shown, the present invention provides a composite material panel, comprising a lower skin layer 2, a polymer foam core material layer 4 and an upper skin layer 1 stacked in sequence from bottom to top;
[0037] The outer surface of the lower skin layer 2 is provided with an impact-resistant coating 6 and a fire-resistant coating 7 in sequence;
[0038] The polymer foam core material layer 4 is provided with a resin column 5, and both end surfaces of the resin column 5 are in contact with the upper skin layer 1 and the lower skin layer 2 respectively;
[0039] It also includes fiber nails 3 passing through the lower skin layer 2 , the polymer foam core layer 4 and the upper skin layer 1 .
[0040] In the present invention, the thickness of the lower skin layer 2 and the upper skin layer 1 is preferably 1.5-3.0 mm independently, and more preferably 2.0-2.5 mm. In the present invention, the lower skin layer 2 and the upper skin layer 1 are preferably independently composed of fiber fabric and resin filled in the fiber fabric structure; the mass percentage of the fiber fabric in the lower skin layer 2 and the upper skin layer 1 is preferably (35-40) ± 3%. In the present invention, the material of the fiber fabric preferably includes one or more of glass fiber, aramid fiber, ultra-high molecular weight polyethylene fiber and basalt fiber. When the material of the fiber fabric is two or more of the above-mentioned specific selections, the present invention does not have any special limitation on the ratio of the above-mentioned specific substances, and they can be mixed in any ratio. In the present invention, the gram weight of the fiber fabric is preferably 400-1000 g / m 2 , more preferably 600g / m 2 ; The fiber fabric is preferably a 3-layer E-glass fiber plain fabric. In the present invention, the resin includes one or more of vinyl resin, epoxy resin and polyurethane resin, and the vinyl resin is preferably bisphenol A epoxy vinyl ester resin; the epoxy resin is preferably bisphenol A epoxy resin; when the resin is two or more of the above specific selections, the present invention has no special restrictions on the ratio of the above specific substances, and they can be mixed in any ratio.
[0041] In the present invention, the upper skin layer 1 and the lower skin layer 2 provide sufficient mechanical properties for the composite material panel while protecting the internal polymer foam core material.
[0042] In the present invention, the thickness of the polymer foam core layer 4 is preferably 3 to 15 mm, more preferably 5 to 12 mm, and most preferably 8 to 10 mm. In the present invention, the density of the polymer foam core in the polymer foam core layer 4 is preferably 70 to 200 kg / m 3 , more preferably 100 to 170 kg / m 3 , the most preferred is 120~150kg / m 3 .
[0043] In the present invention, the foam core material in the polymer foam core layer 4 preferably includes phenolic foam, polyethylene terephthalate foam (PET foam), polyurethane foam or polymethacrylimide foam (PMI foam). In the present invention, the diameter of the resin column 5 in the polymer foam core layer 4 is preferably 0.5-3.0 mm, more preferably 1.0-2.0 mm; the distance between two adjacent resin columns is preferably 20-100 mm, more preferably 40-80 mm, and most preferably 50-70 mm. In the present invention, the resin column 5 is preferably prepared by RTM (resin transfer molding) process injection resin; the RTM (resin transfer molding) process injection resin is preferably vinyl resin, epoxy resin or polyurethane resin.
[0044] In the present invention, the polymer foam core material layer 4 can provide sufficient structural rigidity for the composite material board to ensure that the composite material board does not deform during normal use.
[0045] In the present invention, the thickness of the impact-resistant coating 6 is preferably 0.5 to 3.0 mm, more preferably 1.0 to 2.5 mm, and most preferably 1.5 to 2.0 mm. In the present invention, the material of the impact-resistant coating 6 is preferably polyurea; the polyurea is preferably one or more of polyaspartic acid ester polyurea, aliphatic polyurea and aromatic polyurea. When the polyurea is two or more of the above-mentioned specific selections, the present invention has no special restrictions on the ratio of the above-mentioned specific substances, and they can be mixed in any ratio.
[0046] In the present invention, the impact-resistant layer 6 provides the composite material plate with excellent impact resistance, wear resistance and scratch resistance.
[0047] In the present invention, the thickness of the refractory coating 7 is preferably 0.3-1.5 mm, more preferably 0.8-1.2 mm. In the present invention, the refractory coating 7 preferably includes a high expansion refractory coating or an organic-inorganic refractory coating; in the present invention, the high expansion refractory coating preferably includes a carbonizing agent, a foaming agent, a dehydrating agent and an adhesive; the mass ratio of the carbonizing agent, the foaming agent, the dehydrating agent and the adhesive is preferably (20-40): (10-20): (10-15): (30-40), more preferably 35:15:10:40. The carbonizing agent is preferably a polyhydroxy compound, more preferably starch and / or pentaerythritol; the carbonizing agent is a key substance for forming a carbonaceous layer, which can be dehydrated into carbon at high temperature to provide a skeleton structure for the expanded carbonaceous layer. In the present invention, the foaming agent is preferably a nitrogen-containing compound, more preferably melamine; the foaming agent can be decomposed by heat to produce non-combustible gases such as nitrogen and ammonia, so that the coating expands and foams. In the present invention, the dehydrating agent is preferably ammonium phosphate; the dehydrating agent can promote the dehydration reaction of the carbon forming agent, which is helpful to improve the formation speed and quality of the carbonaceous layer. In the present invention, the adhesive is preferably acrylic resin and / or epoxy resin; the adhesive is used to bond various components together and make the coating firmly adhere to the surface of the substrate. In the present invention, the organic-inorganic refractory coating includes organic components and inorganic components; the mass ratio of the organic resin and the inorganic component is preferably (30-60): (40-70), and more preferably 50:50. In the present invention, the organic resin preferably includes phenolic resin and / or epoxy resin. When the organic resin is two of the above-mentioned specific selections, the present invention does not have any special restrictions on the ratio of the above-mentioned specific substances, and can be mixed in any ratio. In the present invention, the organic resin can form a good chemical bond or physical adsorption between the coating and the substrate surface, enhance the adhesion between the coating and the substrate, ensure that the coating is not easy to fall off or crack during long-term use, and maintain good adhesion performance even when the substrate is subjected to thermal expansion and contraction or external force impact. In the present invention, the inorganic component preferably includes one or more of aluminum oxide, silicon oxide, aluminum hydroxide and magnesium hydroxide. When the inorganic component is two or more of the above specific selections, the present invention has no special restrictions on the ratio of the above specific substances, and can be mixed in any ratio. In the present invention, the inorganic component has a high melting point and high thermal stability, is not easy to melt, decompose, etc. at high temperatures, can withstand high temperature environments, effectively block heat transfer, provide good thermal insulation protection for the substrate, and significantly improve the fire resistance of the substrate.
[0048] In the present invention, the top end of the fiber nail 3 preferably does not exceed the upper surface of the upper skin layer 1, and the bottom end of the fiber nail 3 preferably exceeds the lower surface of the lower skin layer 2. In the present invention, the bottom end of the fiber nail 3 preferably exceeds 1 mm from the lower surface of the lower skin layer 2. The present invention does not have any special restrictions on the positional relationship between the fiber nail and the resin column, as long as the fiber nail 3 and the resin 5 are evenly staggered with each other.
[0049] In the present invention, the diameter of the fiber nail 3 is preferably 0.2-1.0 mm, more preferably 0.28 mm or 0.51 mm. In the present invention, the distance between two adjacent fiber nails 3 is preferably 10-60 mm, more preferably 30-50 mm.
[0050] In the present invention, the material of the fiber nail 3 is preferably a metal material or a non-metal material; the metal material preferably includes stainless steel, aluminum alloy or titanium alloy. The present invention does not have any special restrictions on the types of the aluminum alloy and titanium alloy, and the types familiar to those skilled in the art can be used; the non-metal material preferably includes a fiber-reinforced resin-based composite material; the mass percentage of the fiber in the fiber-reinforced resin-based composite material is preferably 40% to 70%, more preferably 55% to 65%; the fiber is preferably carbon fiber, glass fiber or aramid fiber; the resin matrix in the fiber-reinforced resin-based composite material preferably includes epoxy resin and / or phenolic resin. When the resin is two or more of the above-mentioned specific selections, the present invention does not have any special restrictions on the ratio of the above-mentioned specific substances, and they can be mixed in any ratio.
[0051] In the present invention, the fiber nails 3 connect the upper skin layer 1, the lower skin layer 2 and the polymer foam core layer 4 to form an overall frame structure, which can greatly improve the stiffness and interlayer mechanical properties of the composite material panel structure, thereby greatly improving the impact resistance of the composite material panel.
[0052] The present invention also provides a method for preparing the composite material plate described in the above technical solution, comprising the following steps:
[0053] The lower skin, the sandwich foam with a through-hole structure and the upper skin are sequentially stacked and pre-fixed to obtain a preform;
[0054] implanting fiber nails into the preform, and sequentially performing glue injection and curing molding to obtain an intermediate structure;
[0055] The composite material plate is obtained by spraying an impact-resistant coating and a fire-resistant coating in sequence on the outer surface of the lower skin layer of the intermediate structure.
[0056] The present invention stacks the lower skin, the sandwich foam with a through-hole structure and the upper skin in sequence, and then pre-fixes them to obtain a preformed body.
[0057] In the present invention, the size and spacing of the through holes in the sandwich foam with a through hole structure are preferably the same as the size and spacing of the resin columns.
[0058] In the present invention, the pre-fixing process is preferably to fix the lower skin fiber fabric, the sandwich foam and the upper skin fiber fabric by means of glue spraying.
[0059] After obtaining the preformed body, the present invention implants fiber nails into the preformed body, and sequentially performs glue injection and curing molding to obtain an intermediate structure.
[0060] In the present invention, the method of implanting the fiber nail is preferably the Z-Pinning process. In the present invention, the process of the Z-Pinning process is preferably: placing the preform on a fixture and fixing it firmly, then installing the fiber nail on the chuck of the ultrasonic implantation tool, starting the ultrasonic generator, aligning the implantation tool with the designed implantation position of the preform, and slowly applying pressure to gradually implant the fiber nail into the preform. In the present invention, the vibration frequency of the ultrasonic generator is preferably 20kHz to 50kHz, more preferably 30kHz; the amplitude is preferably 10μm to 50μm, more preferably 30μm. The present invention does not have any special limitation on the process of slowly applying pressure, and a process familiar to those skilled in the art is used to ensure that the fiber nail is smoothly implanted without damaging the preform and the fiber nail body.
[0061] In the present invention, the glue injection is preferably RTM glue injection. In the present invention, the process of RTM glue injection is preferably:
[0062] The preform with fiber nails implanted is placed in the lower mold of the metal mold. During the placement process, the fiber nail preform should be prevented from deformation or damage. A positioning device is used to ensure that the preform is positioned accurately in the mold. After the preform is laid up, the preform is corrected to meet the RTM process requirements. Finally, the upper mold of the mold is installed in place to make the entire mold cavity airtight and sealed.
[0063] Add the raw materials for preparing the resin into the storage tank of the RTM injection machine, connect the injection port of the RTM with the injection port of the mold, ensure a tight connection to prevent resin leakage, start the RTM injection machine, and inject the raw materials for preparing the resin into the mold cavity.
[0064] In the present invention, the pressure of the RTM injection machine is preferably 0.2-1.0 MPa, more preferably 0.3 MPa; the flow rate is preferably 50-500 mL / s, more preferably 100 mL / s.
[0065] In the present invention, during the injection process, it is preferred to pay attention to observing the flow of the resin, which can be monitored through a transparent observation window provided on the mold to ensure that the resin flows evenly in the fiber nail preform and gradually fills the entire mold cavity.
[0066] In the present invention, the curing temperature is preferably 80-120° C., more preferably 100° C.; the curing time is preferably 5-20 min, more preferably 10 min.
[0067] In the present invention, during the curing process, it is preferred to ensure that the temperature distribution in the mold is uniform to ensure that the resin is fully cured.
[0068] After the curing and molding is completed, the present invention also preferably includes demoulding. The present invention does not have any special limitation on the demoulding process, and the demoulding process is performed using a process well known to those skilled in the art.
[0069] After the demoulding is completed, the present invention also preferably includes post-processing, and the post-processing preferably includes trimming, drilling and grinding the surface of the lower skin layer in sequence; the present invention does not have any special limitations on the process of trimming, drilling and grinding, and can be carried out using the process familiar to those skilled in the art.
[0070] After the intermediate structure is obtained, the present invention sequentially sprays an impact-resistant coating and a fire-resistant coating on the outer surface of the lower skin layer of the intermediate structure to obtain the composite material plate.
[0071] In the present invention, before the spraying, it is preferred to sequentially clean and dry the surface of the lower skin layer after polishing, and the cleaning process is preferably to thoroughly clean the surface of the polished lower skin layer to remove impurities such as oil and dust, and then wipe it with an organic solvent. The present invention does not have any special limitation on the drying process, and it can be carried out using a process well known to those skilled in the art.
[0072] When spraying the impact-resistant coating, the distance between the spray gun and the sprayed surface is preferably 40 to 80 cm, the moving speed during spraying is preferably 0.1 to 0.3 m / s, and the pressure of the spray gun is preferably 10 to 30 MPa; the curing time after the spraying is completed is preferably ≤60 s, and the curing temperature after the spraying is completed is preferably 30°C.
[0073] When spraying the refractory coating, the distance between the spray gun and the sprayed surface is preferably 40 to 80 cm, the moving speed during spraying is preferably 0.1 to 0.3 m / s, and the pressure of the spray gun is preferably 0.8 to 3.0 MPa; the curing time after the spraying is completed is preferably 2 hours, and the curing temperature after the spraying is completed is preferably 60°C.
[0074] In the present invention, when the bottom surface area of the lower skin layer is large, it is preferably carried out in a criss-cross manner, that is, spraying is first performed along one direction (such as the horizontal direction) to form a uniform coating layer, and then a second spraying is performed in a direction perpendicular to the first layer to ensure the uniformity and integrity of the coating.
[0075] The present invention also provides the use of the composite material plate described in the above technical solution or the composite material plate prepared by the preparation method described in the above technical solution in new energy vehicles. In the present invention, the upper skin layer of the composite material plate is in contact with the battery pack.
[0076] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0077] Example 1
[0078] like Figure 1 As shown, the structure of the composite material panel: a lower skin layer 2, a polymer foam core layer 4 and an upper skin layer 1 are stacked in sequence from bottom to top; the outer surface of the lower skin layer 2 is sequentially provided with an impact-resistant coating 6 and a fire-resistant coating 7; a resin column 5 is provided in the foam core layer 4, and the two end surfaces of the resin column 5 are in contact with the upper skin layer 1 and the lower skin layer 2 respectively; the lower skin layer 2, the polymer foam core layer 4 and the upper skin layer 1 are fixed by fiber nails 3; the lower skin layer 2 includes a gram weight of 600g / m 2 The three layers of E-glass fiber plain fabric (thickness of 1.5 mm) and the resin (epoxy vinyl ester resin) filled in the three layers of E-glass fiber plain fabric, wherein the mass percentage of the three layers of E-glass fiber plain fabric in the lower skin layer 2 is 35±3%; the upper skin layer 1 includes a gram weight of 600g / m 2 The polymer foam core layer 4 comprises phenolic foam and resin columns 5 filled in the through-hole structure of the phenolic foam, and the two end surfaces of the resin columns 5 are in contact with the upper skin layer 1 and the lower skin layer 2 respectively. The thickness of the phenolic foam is 10 mm and the density is 100 kg / m 3, the diameter of the resin column 5 is 2.0mm, the spacing between two adjacent resin columns 5 is 25mm, and the material of the resin column 5 is epoxy resin; the diameter of the fiber nail 3 is 0.28mm, and the distance between two adjacent fiber nails 3 is 50mm; the upper end of the fiber nail 3 does not exceed the upper surface of the upper skin layer 1, and the lower end of the fiber nail 3 exceeds the lower surface of the lower skin layer 2 by 1mm; the material of the fiber nail 3 is carbon fiber / epoxy resin composite material; the thickness of the impact-resistant coating 6 is 1.5mm, and the material is polyurea (specifically aspartic acid ester polyurea); the thickness of the fire-resistant coating 7 is 1.0mm, and it is specifically a high-expansion fire-resistant coating (the material includes a carbon forming agent (type is phenolic resin), a foaming agent (type is melamine), a dehydrating agent (type is ammonium polyphosphate) and an adhesive (type is epoxy resin) in a mass ratio of 35:15:10:40);
[0079] Preparation process of composite material board: two 3-layer E-glass fiber plain fabrics (weight 600g / m 2 ) as the fiber fabric of the upper skin layer and the lower skin layer; the thickness is 10mm and the density is 100kg / m 3 The phenolic foam is used as the sandwich foam, and the sandwich foam includes uniformly arranged through holes, the hole diameter of the through holes is 2.0 mm, and the distance between two adjacent through holes is 25 mm;
[0080] After stacking the lower skin fiber fabric, the sandwich foam and the upper skin fiber fabric in sequence, the layers are pre-fixed by spraying glue to obtain a preform;
[0081] The preform is placed on a suitable fixture to ensure that it is firmly fixed, and then a fiber nail with a diameter of 0.28 mm (made of carbon fiber reinforced epoxy resin composite material, the mass percentage of carbon fiber in the carbon fiber reinforced epoxy resin composite material is (60±5)%) is installed on the chuck of the ultrasonic implantation tool, and the ultrasonic generator is started, and the vibration frequency is adjusted to 30 kHz and the amplitude is 30 μm. Then, the implantation tool is aligned with the pre-designed implantation position in the preform (the spacing between two adjacent fiber nails is 50 mm), and pressure is slowly applied to gradually implant the fiber nail into the preform, and it is ensured that the fiber nail is successfully implanted without damaging the preform and the fiber nail body, so as to obtain a fiber nail preform;
[0082] The fiber nail preform is placed in the lower mold of the metal mold. During the placement process, the fiber nail preform is prevented from being deformed or damaged. A positioning device is used to ensure that the position of the preform in the mold is accurate. The layering of the preform is corrected to ensure that the requirements of the RTM injection process are met. Then, the upper mold of the mold is installed in place to make the entire mold cavity airtight and sealed.
[0083] Select an epoxy vinyl ester resin curing system, add epoxy vinyl ester resin (epoxy vinyl ester resin) and curing agent (tert-butyl hydroperoxide) into the storage tank of RTM injection agent according to the mass ratio of 100:1, connect the injection port of RTM with the injection port of the mold, ensure that the connection is tight, prevent resin leakage, set appropriate pressure (0.3MPa) and flow rate (100mL / s) in the system, start the RTM machine to continuously inject the resin into the mold cavity, monitor the flow of the resin through the transparent observation window set on the mold during the injection process, make the resin flow evenly in the fiber nail preform and gradually fill the entire mold cavity, then cure at 100°C for 10min, demould, and obtain a composite blank;
[0084] After trimming, drilling and polishing the surface of the lower skin of the composite material blank in sequence, the polished lower skin surface is thoroughly cleaned to remove impurities such as oil and dust, wiped with an organic solvent, and dried, and the two components of aspartic acid ester polyurea (component A with a mass ratio of 1:1.2 (isocyanate prepolymer and auxiliary agent with a mass ratio of 100:0.5 (the type of auxiliary agent is silicone defoamer and silicone leveling agent with a mass ratio of 1:1)) and component B (amine with a mass ratio of 100:50:100) A chain extender (the type of amine chain extender is aspartic acid ester secondary amine chain extender), a crosslinker (the type of crosslinker is a polyisocyanate crosslinker) and a filler (the type of filler is silicon dioxide))) are fully mixed under high pressure, and the coating obtained after the mixture is sprayed with a spray gun (the spraying pressure is 15 MPa, the distance between the spray gun and the sprayed surface is 50 cm, and the moving speed of the spray gun is 0.2 m / s) to a thickness of 1.5 mm, and then cured (the curing temperature is 30° C. and the time is 60 s) to obtain an impact-resistant coating;
[0085] A carbon former (pentaerythritol), a foaming agent (melamine), a dehydrating agent (ammonium phosphate) and an adhesive (epoxy resin) are stirred and mixed in a mass ratio of 35:15:10:40, and the mixed coating is sprayed with a spray gun (the spraying pressure is 0.5 MPa, the distance between the spray gun and the sprayed surface is 50 cm, and the moving speed of the spray gun is 0.2 m / s) to a thickness of 1.0 mm, and then cured (the curing temperature is 60°C and the time is 2 hours) to obtain a fire-resistant coating, and then a composite material board is obtained.
[0086] Example 2
[0087] like Figure 1As shown, the structure of the composite material panel: a lower skin layer 2, a polymer foam core layer 4 and an upper skin layer 1 are stacked in sequence from bottom to top; the outer surface of the lower skin layer 2 is sequentially provided with an impact-resistant coating 6 and a fire-resistant coating 7; a resin column 5 is provided in the polymer foam core layer 4, and the two end surfaces of the resin column 5 are in contact with the upper skin layer 1 and the lower skin layer 2 respectively; the lower skin layer 2, the polymer foam core layer 4 and the upper skin layer 1 are fixed by fiber nails 3; the lower skin layer 2 includes 4 layers with a gram weight of 600g / m 2 Aramid fiber plain fabric (thickness of 2.0 mm) and cured resin (bisphenol A epoxy resin) filled in the 6 layers of aramid fiber plain fabric, wherein the mass percentage of the 6 layers of aramid fiber plain fabric in the lower skin layer 2 is 40%; the upper skin layer 1 includes a gram weight of 400 g / m 2 Aramid fiber plain weave fabric (thickness of 2.0 mm) and resin (bisphenol A epoxy resin) filled in the aramid fiber plain weave fabric, wherein the mass percentage of the aramid fiber plain weave fabric in the upper skin layer 1 is 40%; the polymer foam core layer 4 includes PET foam and resin columns 5 filled in the through-hole structure of the PET foam, the resin columns 5 run through the thickness direction of the PET foam, the thickness of the PET foam is 12 mm, and the density is 120 kg / m 3 , the diameter of the resin column 5 is 2.0mm, the spacing between two adjacent resin columns 5 is 25mm, and the material of the resin column 5 is epoxy resin; the diameter of the fiber nail 3 is 0.51mm, and the distance between two adjacent fiber nails 3 is 40mm; the upper end of the fiber nail 3 does not exceed the upper surface of the upper skin layer 1, and the lower end of the fiber nail 3 exceeds the lower surface of the lower skin layer 2 by 1mm; the material of the fiber nail 5 is carbon fiber / epoxy resin composite material (the material is carbon fiber reinforced epoxy resin composite material, and the mass percentage of carbon fiber in the carbon fiber reinforced epoxy resin composite material is (60±5)%); the thickness of the impact-resistant coating 6 is 2.0mm, and the material is polyurea (specifically polyaspartic acid ester polyurea); the thickness of the fire-resistant coating 7 is 0.3mm, and it is specifically an organic-inorganic fire-resistant coating (the material includes an organic component (phenolic resin) and an inorganic component (aluminum hydroxide) in a mass ratio of 50:50);
[0088] Preparation process of composite material board: two pieces of 4-layer aramid fiber plain weave cloth (weight 600g / m 2 ) as the fiber fabric of the upper skin layer and the lower skin layer; the thickness is 12mm and the density is 120kg / m 3 PET foam is used as the sandwich foam, and the sandwich foam includes evenly arranged through holes, the hole diameter of the through holes is 2.0 mm, and the distance between two adjacent through holes is 25 mm;
[0089] After stacking the lower skin fiber fabric, the sandwich foam and the upper skin fiber fabric in sequence, the layers are pre-fixed by spraying glue to obtain a preform;
[0090] The preform is placed on a suitable fixture to ensure that it is firmly fixed, and then a fiber nail with a diameter of 0.51 mm is installed on the chuck of the ultrasonic implantation tool, and the ultrasonic generator is started, and the vibration frequency is adjusted to 35 kHz and the amplitude is 40 μm. Then, the implantation tool is aligned with the pre-designed implantation position in the preform, and pressure is slowly applied to gradually implant the fiber nail into the preform, and it is ensured that the fiber nail is successfully implanted without damaging the preform and the fiber nail body, so as to obtain a fiber nail preform;
[0091] The fiber nail preform is placed in the lower mold of the metal mold. During the placement process, the fiber nail preform is prevented from being deformed or damaged. A positioning device is used to ensure that the position of the preform in the mold is accurate. The layering of the preform is corrected to ensure that the requirements of the RTM injection process are met. Then, the upper mold of the mold is installed in place to make the entire mold cavity airtight and sealed.
[0092] Select an epoxy resin curing system, add component A and component B (component A is bisphenol A epoxy resin, component B is amine curing agent (specific type is 793 curing agent)) into the storage tank of RTM injection agent according to a mass ratio of 100:30, connect the injection port of RTM with the injection port of the mold, ensure that the connection is tight, prevent resin leakage, set appropriate pressure (0.7MPa) and flow rate (200mL / s) in the system, start the RTM machine to continuously inject the resin into the mold cavity, monitor the flow of the resin through a transparent observation window set on the mold during the injection process, and make the resin flow evenly in the fiber nail preform to gradually fill the entire mold cavity, and then cure it at 120°C for 15min, demould, and obtain a composite material blank;
[0093] After trimming, drilling and polishing the surface of the lower skin of the composite material blank in sequence, the polished lower skin surface is thoroughly cleaned to remove impurities such as oil and dust, wiped with an organic solvent, and dried, and the two components of aspartic acid ester polyurea (component A with a mass ratio of 1:1.2 (isocyanate prepolymer and auxiliary agent with a mass ratio of 100:0.5 (the type of auxiliary agent is silicone defoamer and silicone leveling agent with a mass ratio of 1:1)) and component B (amine with a mass ratio of 100:50:100) A chain extender (the type of amine chain extender is aspartic acid ester secondary amine chain extender), a crosslinker (the type of crosslinker is a polyisocyanate crosslinker) and a filler (the type of filler is silicon dioxide) are fully mixed under high pressure, and the coating obtained after the mixture is sprayed with a spray gun (the spraying pressure is 15 MPa, the distance between the spray gun and the sprayed surface is 50 cm, and the moving speed of the spray gun is 0.2 m / s) to a thickness of 2.0 mm, and then cured (the curing temperature is 30° C. and the time is 60 s) to obtain an impact-resistant coating;
[0094] The organic resin and the inorganic component are stirred and mixed in a mass ratio of 50:50, and the mixed coating is sprayed with a spray gun (the spraying pressure is 0.5 MPa, the distance between the spray gun and the sprayed surface is 50 cm, and the moving speed of the spray gun is 0.2 m / s) to a thickness of 0.3 mm, and then cured (the curing temperature is 80°C and the time is 4 hours) to obtain a fire-resistant coating, and then a composite material board is obtained.
[0095] Comparative Example 1
[0096] like Figure 6 As shown, the structure of the composite material panel includes a lower skin layer 10 (thickness 1.2 mm, made of E-glass fiber plain fabric and vinyl ester resin), a foam core layer 9 (thickness 15 mm, made of PET foam, density 120 kg / m 3 ) and an upper skin layer 8 (1.2 mm thick, made of E-glass fiber plain weave fabric and vinyl ester resin);
[0097] Preparation method of composite material board: using press molding process:
[0098] First, the 4 layers of 400g / m 2 E-glass fiber plain fabric / vinyl ester resin prepreg are stacked in sequence, 15mm thick PET foam is laid on the upper surface of the lower skin, and then 4 layers of 400g / m 2 The E-glass fiber plain cloth fabric / vinyl ester resin prepreg is laid on the PET foam in sequence to form a preformed sandwich structure.
[0099] Then, the preformed sandwich structure is placed in the lower mold cavity of the press, the upper mold cavity is closed, the press is pressurized to 600t, and after being kept at 120°C for 10 minutes, the prepreg is completely cured and demolded to obtain the product blank.
[0100] Test Case
[0101] With reference to GB / T 14153 standard, the impact head is a φ25 mm hemisphere, and the composite material panels described in Example 1 and Comparative Example 1 are subjected to a 400 J drop hammer impact test. Figure 2 This is a graph showing the effect of the composite material plate in Example 1 in resisting a 400J drop hammer impact test. Figure 3 This is a graph showing the effect of the composite material plate of Comparative Example 1 on resisting a 180J drop hammer impact test. Figures 2-3 It can be seen that after the 400J impact, the coating and lower skin of the composite material plate of Example 1 were damaged, and the upper skin was intact; while the comparative example 1 was penetrated when the impact energy was 180J;
[0102] The composite material plates described in Example 1 and Comparative Example 1 were subjected to a fire test at 1200°C for 360 seconds using an acetylene flame. Figure 4 This is a 1200°C×360s fire test effect diagram of the composite material plate described in Example 1. Figure 5 This is a 1200°C × 360s fire test effect diagram of the composite material plate described in Comparative Example 1. Figures 4-5 It can be seen that the back side of Example 1 was not burned through in the 1200°C×360s fire test; while Comparative Example 1 was burned through at 120s of the 1200°C×360s fire test.
[0103] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A composite material board, characterized in that: It comprises a lower skin layer (2), a polymer foam core material layer (4) and an upper skin layer (1) which are stacked in sequence from bottom to top; The outer surface of the lower skin layer (2) is provided with an impact-resistant coating (6) and a fire-resistant coating (7) in sequence; A resin column (5) is provided in the polymer foam core material layer (4), and both end surfaces of the resin column (5) are in contact with the upper skin layer (1) and the lower skin layer (2) respectively; It also includes fiber nails (3) passing through the lower skin layer (2), the polymer foam core layer (4) and the upper skin layer (1).
2. The composite material plate according to claim 1, characterized in that: The impact-resistant coating (6) is a polyurea coating; The thickness of the impact-resistant coating (6) is 0.5 to 3.0 mm.
3. The composite material plate according to claim 1, characterized in that: The thickness of the refractory coating (7) is 0.3 to 1.5 mm; The refractory coating (7) comprises a high expansion type refractory coating or an organic-inorganic type refractory coating.
4. The composite material plate according to claim 1, characterized in that: The top end of the fiber nail (3) does not exceed the upper surface of the upper skin layer (1), and the bottom end of the fiber nail (3) exceeds the lower surface of the lower skin layer (2); The diameter of the fiber nail (3) is 0.2-1.0 mm, and the distance between two adjacent fiber nails (3) is 10-60 mm.
5. The composite material plate according to claim 1, characterized in that: The thickness of the lower skin layer (2) and the upper skin layer (1) are independently 1.5 to 3.0 mm.
6. The composite material plate according to claim 5, characterized in that The lower skin layer (2) and the upper skin layer (1) independently include fiber fabrics and resin filled in the fiber fabrics; The material of the fiber fabric includes one or more of glass fiber, aramid fiber, ultra-high molecular weight polyethylene fiber and basalt fiber; The resin includes one or more of vinyl resin, epoxy resin and polyurethane resin.
7. The composite material plate according to claim 1, characterized in that: The thickness of the polymer foam core layer (4) is 3 to 15 mm; The density of the foam core material in the polymer foam core material layer (4) is 70 to 200 kg / m 3 .
8. The composite material plate according to claim 1 or 7, characterized in that: The material of the polymer foam core layer (4) includes phenolic foam, polyethylene terephthalate foam, polyurethane foam or polymethacrylimide foam; The diameter of the resin column (5) in the polymer foam core material layer (4) is 0.5 to 3.0 mm, and the distance between two adjacent resin columns (5) is 20 to 100 mm.
9. The method for preparing the composite material plate according to any one of claims 1 to 8, characterized in that: The following steps are involved: The lower skin, the sandwich foam with a through-hole structure and the upper skin are sequentially stacked and pre-fixed to obtain a preform; implanting fiber nails into the preform, and sequentially performing glue injection and curing molding to obtain an intermediate structure; The composite material plate is obtained by spraying an impact-resistant coating and a fire-resistant coating in sequence on the outer surface of the lower skin layer of the intermediate structure.
10. Use of the composite material plate according to any one of claims 1 to 8 or the composite material plate prepared by the preparation method according to claim 9 in new energy vehicles.
Citation Information
Patent Citations
Pin-type load-bearing / protection integrated high-strength polyethylene composite armored bulkhead structure
CN109131724A
Integrated foam sandwich structure and enhancing method thereof
CN111038007A
Impact-resistant composite material plate for heavy-duty truck carriage body as well as preparation method and application of impact-resistant composite material plate
CN116803678A
Composite material anti-collision structure and bogie
CN214874819U